Legal Aspects of Labor Regulation for Individuals Performing Non-Standard Employment Functions - Zharkenova, S.B.; Galiakbarova, G.G. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
Changes brought about by digitalization and the introduction of artificial intelligence into our lives require new approaches to regulating labor relations, in particular, expanding the role of the employment contract in regulating labor relations, including those arising in the sphere of non-standard employment. This article examines the problematic aspects of labor regulation for individuals performing non-standard work, including digital nomads. Currently, labor law scholarship and the labor legislation of the Republic of Kazakhstan (hereinafter referred to as RK) lack a unified concept of what constitutes non-standard employment or what forms such employment takes. Consequently, there is no systematization of these types of labor activity. The legal status of digital nomads remains poorly understood. Therefore, this article focuses on ideas aimed at developing a national concept for digital nomads, which should help overcome gaps in the legislative regulation of this form of employment. An analysis of labor legislation aimed at expanding the role of the employment contract in the sphere of non-standard employment allowed us to examine the capabilities of the existing electronic unified system for recording employment contracts and identify some shortcomings in its operation. This article was based on current national codified legal acts, as well as materials obtained during the project work. An analysis of individual provisions of these documents allowed identifying problematic aspects of current labor legislation, leading to recommendations for its further improvement. The authors’ ideas presented in the article can be used to develop a concept for legal regulation of precarious employment, including digital nomadism.